Increasing returns and labour markets in a predator-prey model - Giovanni Dosi; Davide Usula; Maria Enrica Virgillito (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2023)
The purpose of this work is to study the joint interaction of three founding elements of modern capitalism, namely endogenous technical change, income distribution and labour markets, within a low-dimensional nonlinear dynamic setup extending the Goodwin model. By going beyond the conservative structure typical of the predator-prey model, we insert an endogenous source of energy, namely a Kaldor-Verdoon increasing returns specification, that feeds the dynamics of the system over the long run and in that incorporates a transition to an (anti) dissipative framework. The qualitatively dynamics and ample array of topological structures reflect a wide range of Kaldorian stylised facts, as steady productivity growth and constant income distribution shares. The intensity of learning regimes and wage sensitivity to unemployment allow to mimic some typical traits of both Competitive and Fordist regimes of accumulation, showing the relevance of the demand-side engine, represented by the KV law, within an overall supply-side framework. High degrees of learning regimes stabilise the system and bring it out of an oscillatory trap. Even under regimes characterised by low degrees of learning, wage rigidity is able to stabilise the business cycle fluctuations and exert a positive effect on productivity growth.
Keywords: C61; C63; E11; E12; E32; E37; 330; Capitalist system; Kaldor-Verdoon law; wage rigidity; dissipative complex systems